2019
DOI: 10.5430/ijfr.v10n5p381
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Social Responsibility in Malaysia

Abstract: The field of corporate social responsibility (CSR) has developed exponentially in the last decade and is consistently getting to be a worldwide slant. Corporate social responsibility (CSR) has become a worldwide matter around the world that comes about an expanding number of studies on CSR universally as well as in Malaysia. Furthermore, the importance of CSR practices was emphasized by companies in order to ensure its sustainability in corporate world which are focused on (a) environment, (b) social dimension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 16 publications
0
10
0
1
Order By: Relevance
“…Nurjanah (2019) claimed that CSR in Malaysia is mostly dominated by charity activities, and those activities with a focus on reducing environmental damage are still very minimal. In another studies, Hizam et al. (2019) and Ismail et al.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…Nurjanah (2019) claimed that CSR in Malaysia is mostly dominated by charity activities, and those activities with a focus on reducing environmental damage are still very minimal. In another studies, Hizam et al. (2019) and Ismail et al.…”
Section: Discussionmentioning
confidence: 90%
“…Nurjanah (2019) claimed that CSR in Malaysia is mostly dominated by charity activities, and those activities with a focus on reducing environmental damage are still very minimal. In another studies, Hizam et al (2019) and Ismail et al (2014) found that high percentage of the sampled managers and leaders in Malaysia do not fully appreciate the importance of CSR, while are relatively aware of CSR programs. Accordingly, more experimental research are needed on the practical benefits of CSR at the corporate and national levels.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…When a company is committed to its social responsibilities, it can disclose it to stakeholders (Wang & Sarkis, 2017;Advantage, 2020). This allows stakeholders and the community to distinguish such companies from other companies (Bessong & Tapang, 2012;Hizam et al, 2019). Corporate Social Responsibility Reporting or Corporate Social Responsibility Disclosure and Disclosure of Environmental and Social Information in Annual Reports and Websites is gaining popularity.…”
Section: Introductionmentioning
confidence: 99%